STATISTICAL ANALYSIS OF AGRICULTURE PRODUCTION PERFORMANCE AND DEVELOPMENT IN RAJASTHAN - Dr.Anita Choudhary (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Though showering with diversified climatic conditions for agriculture, Rajasthan state is abundantly involved religiously in farming of various crops along with resilient agriculture sector. Agriculture remains to be the strength of the State’s frugality with Agriculture & allied sectors backing 25.56% of entire GSDP in 2019-20. Secondary data related to agricultural development has been extracted from various government publications and then compiled for the analysis. Correlation analysis was done to investigate which research variables are correlated and up to what extent. Also multiple regression analysis was done so as to understand the impact of all independent variables of agriculture production performance and development on cropping intensity, the dependent variable for the current study.